5PSQ-121 Pharmaceutical intervention in conciliation performed in an emergency department. (2nd March 2018) - Florit, M; Fernandez, M; Molas, G; García, M
Abstract : Background: Medication errors are common in the hospital setting and especially in the Emergency Department (ED), leading to an increase in mortality, morbidity and economic costs. It is recognised that the role of the pharmacist in the conciliation process at the ED improves this situation. In our hospital, with the aim of reducing the number of medication errors, a pharmacist reviews the medication of patients who stay more than 24 hours in the emergency room, who are pending admission or are admitted to a short-stay ward within the ED. Purpose: To describe the pharmaceutical interventions (PI) made during the conciliation process, the drugs involved and the degree of acceptance of the intervention by the prescriber. Material and methods: Retrospective descriptive observational study of data collected from May to September 2017. The pharmacist spends 1 to 2 hours from Monday to Friday in the emergency service to perform the conciliation. The PI performed are registered in a database and communicated to the responsible physicians. Data collected: type of PI, drugs involved and acceptance of the recommendation by the prescriber. Results: A total of 345 PI were recorded in 220 patients (124 males, 80. 4±9.3 mean age). The mean of PI for patients was 1.56. The most frequently PI performed were: 124 (35.9%) related to indication (either by omission or contraindication), 68 (19.7%) dose adjustments, 58 (16.8%) changes to a therapeutic equivalent and 47 (13.6%) evaluation of restricted drugs. Other types of PI were less frequent (<20). The most commonly involved drugs were: 46 (13.3%) anticoagulants, 33 (9.6%) hypolipemiants, 31 antidepressants (9%) and 22 (6.4%) respiratory drugs. The degree of acceptance of PI were: 220 (63.8%) accepted, 28 (8.1%) rejected and 97 (28.1%) not evaluated due to discharge of the patient before the resolution of PI. Conclusion: The most frequent PI performed were related to indication. The most commonly involved drugs were anticoagulants. The degree of acceptance of the PI by the prescribers was high. The conciliation process carried out by the pharmacist helps to reduce medication errors. References and/or Acknowledgements: 1. Med Clin ( Barc) 2015;145(7):288–93. 2. Farm Hosp2014;38(5):430–437. 3. Emergencias 2013;25:204–217. No conflict of interest